Modified Metal−Organic Frameworks for Electrochemical Applications. Issue 5 (10th February 2022) - Chen, Kefan; Wang, Xiao-Li; Hu, Wenhui; Kong, Qingquan; Pang, Huan; Xu, Qiang
Abstract : Metal−organic frameworks (MOFs) are neo‐type porous materials synthesized via organic ligands and metal ions, which have drawn much attention due to their unparalleled advantages such as high specific surface area, large and clear pore structures, and uniformly distributed active sites. In these years, modified MOFs are regarded as kinds of materials with excellent electrochemical properties, that overcome poor conductivity and stability of original MOFs and narrow the gap between the basic science of MOFs and their future applications. At the same time, it also provides an opportunity to elaborate the synergistic effect of the synthesis strategy of modified MOFs on the performance. This review focuses on the synthesis, structure characterization, and electrochemical adhibition of modified MOFs and discusses the challenges and application prospects of modified MOFs in energy storage and conversion. Abstract : Modified MOFs have excellent electrochemical properties and provide great opportunities to solve the problems of energy storage and conversion. This article reviews the research progress of modified MOFs, including their synthesis, structural characterization, and electrochemical applications, and focuses on the synthesis strategies and synergistic effects of modified MOFs on their properties.